A Circuit for the Square Root of the Sum of Two Squared Voltages using an IC LM311 Open Collector Comparator - Selvam, K. C. (Engineering, Technology & Applied Science Research, 2013)
A circuit which accepts two input dc voltages V1 and V2 and provides an output dc voltage VO equal to the square root of the sum of the two squared voltages of V1 and V2, using an LM311 open collector comparator based single quadrant time division multiplier is described in this paper.